The theories, laws and practice of juvenile/child justice system in Nigeria (2016)
This chapter in this book seeks to exermine the different theories and causes of juvenile deliquency, with the aim of enhancing legal education for both the teacher and the students, towards building a better oriented society for the child and the adult on the short term and a crime free society on the long term